2021
DOI: 10.1038/s41598-020-80074-x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal enhancement of phosphorus uptake and yields of maize under high planting density in the black soil region of China

Abstract: Arbuscular mycorrhizal (AM) symbioses are an attractive means of improving the efficiency of soil phosphorus (P) that difficult to be used by plants and may provide a sustainable way of maintaining high yields while reducing P applications. However, quantifying the contribution of indigenous AM fungi on phosphorus uptake and yields of maize (Zea mays L.) under field conditions is not particularly clear. Mesh-barrier compartments were applied to monitor the distribution of hyphal P uptake throughout the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…For example, PUE in maize production can be improved by manipulating the root morphology and AM colonization to maintain an appropriate P supply intensity in the root zone (Deng et al, 2017 ; Kobae, 2019 ; Chu et al, 2020 ). Similarly, maintaining space for proper root growth in intensive high-plant-density maize production systems could modify the root morphology and AM colonization to enhance maize yield (Yu et al, 2019 ; Hou et al, 2021 ). However, most of the previous studies in high-density planting systems have focused on the regulation of root morphology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PUE in maize production can be improved by manipulating the root morphology and AM colonization to maintain an appropriate P supply intensity in the root zone (Deng et al, 2017 ; Kobae, 2019 ; Chu et al, 2020 ). Similarly, maintaining space for proper root growth in intensive high-plant-density maize production systems could modify the root morphology and AM colonization to enhance maize yield (Yu et al, 2019 ; Hou et al, 2021 ). However, most of the previous studies in high-density planting systems have focused on the regulation of root morphology.…”
Section: Introductionmentioning
confidence: 99%
“…However, once sucrose reaches the arbuscular mycorrhized (AM) root, some specific type II transporters seem to return sugars back towards the plant cells (Bitterlich et al., 2014), thus suggesting that there can be a mechanism of reverse transport to influence symbiotic fungal growth. Experimental studies have reported the key roles of arbuscular mycorrhizas (AM) and ectomycorrhizas (EM) in increasing plant P uptake (Caris et al., 1998; Etesami et al., 2021; Hou et al., 2021), and it has been suggested that most plant species can improve their ability to take up highly immobile soil P by symbiosis with mycorrhizal fungi (Albornoz et al., 2021; Smith & Read, 2008). Mycorrhizas are less important for more mobile macronutrients such as N that are readily taken up by roots (Lambers et al., 2008).…”
Section: Consistent Role Of Mycorrhizas and Root Exudates In Phosphor...mentioning
confidence: 99%
“…Nấm rễ AM có khả năng thúc đẩy sự hấp thu các chất dinh dưỡng khoáng như đạm (N), lân (P), kali (K), kẽm (Zn), đồng (Cu) trong hầu hết các loại cây trồng [2,5,23], đặc biệt là hiệu quả trong việc giúp cây trồng tăng khả năng hấp thu chất dinh dưỡng trong đất bị thiếu hụt dinh dưỡng, nhất là P [20,24]. Nấm AM là một phương tiện hữu hiệu để cây trồng khai thác dạng P khó tiêu trong đất và có thể cung cấp một cách bền vững để duy trì năng suất cao khi giảm lượng phân lân bón vào đất [24,25].…”
Section: Nấm Am Và Dinh Dưỡng Khoángunclassified